Pengaruh Kecerdasan Logis-Matematis Terhadap Hasil Belajar Matematika Pada Siswa Kelas VII Di MTSN 2 Padangsidimpuan - Sari, Lili Nur Indah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
The formulation of the problem in this study is whether there is the influence of logical-mathematical intelligence on the learning outcomes of class VII students of Padangsidimpuan MTsN 2? The purpose of this study was to determine the effect of logical-mathematical intelligence on the mathematics learning outcomes of class VII students of Padangsidimpuan 2 MTsN.This research includes the type of quantitative research using the Ex Post Facto method. The population in this study were VII grade students of MtsN 2 Padangsidimpuan which numbered 211 students while the sample was all students who took the test of Logical-Mathematical Intelligence which amounted to 211 people. The data collection method used is a test with data analysis techniques namely t test.The results showed that: There was a significant influence between logical-mathematical intelligence and the mathematics learning outcomes of class VII students of Padangsidimpuan MTsN 2 as evidenced by the results of the t test of 17.137 greater than the t table of 1.98 (17.137 1.98) which means there are differences in learning outcomes of students who have high logical-mathematical intelligence with students who have low logical-mathematical intelligence. So that it can be concluded that there is a significant influence between Logical-Mathematical intelligence variables and mathematics learning outcomes where students who have high logical-mathematical intelligence, the learning outcomes are high and vice versa.Â